2023
DOI: 10.1021/acsbiomaterials.3c00369
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Therapeutic siRNA Delivery and Imaging by Nitrogen- and Neodymium-Doped Graphene Quantum Dots

Alina R. Valimukhametova,
Bong Han Lee,
Ugur C. Topkiran
et al.

Abstract: While small interfering RNA (siRNA) technology has become a powerful tool that can enable cancer-specific gene therapy, its translation to the clinic is still hampered by the inability of the genes alone to cell transfection, poor siRNA stability in blood, and the lack of delivery tracking capabilities. Recently, graphene quantum dots (GQDs) have emerged as a novel platform allowing targeted drug delivery and fluorescence image tracking in visible and near-infrared regions. These capabilities can aid in overco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…In terms of cell compatibility, while certain in vitro experiments have shown that C 2 N exhibits cytotoxicity, such as inducing oxidative stress in vascular endothelial cells, 30 significantly inhibiting the proliferation of bladder cancer cells, 31 and causing ferroptosis and inflammatory responses in BV2 microglial cell line, 32,33 other experiments have demonstrated good cell membrane compatibility of C2N, with no effect on blood cell hemolysis, 34 no toxicity to breast cancer cells, 35 and no harm to Wistar albino rats 22 . In summary, C2N has emerged as an important nanomaterial with a wide range of applications in the field of biomedicine 36–42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of cell compatibility, while certain in vitro experiments have shown that C 2 N exhibits cytotoxicity, such as inducing oxidative stress in vascular endothelial cells, 30 significantly inhibiting the proliferation of bladder cancer cells, 31 and causing ferroptosis and inflammatory responses in BV2 microglial cell line, 32,33 other experiments have demonstrated good cell membrane compatibility of C2N, with no effect on blood cell hemolysis, 34 no toxicity to breast cancer cells, 35 and no harm to Wistar albino rats 22 . In summary, C2N has emerged as an important nanomaterial with a wide range of applications in the field of biomedicine 36–42 …”
Section: Discussionmentioning
confidence: 99%
“…22 In summary, C2N has emerged as an important nanomaterial with a wide range of applications in the field of biomedicine. [36][37][38][39][40][41][42] In our study, we employed GO as a widely used control to perform a systematic comparison of the lethal dosage, tissue distribution, inflammation, and cell injury induced by intravenous administration GO/C 2 N in mice. We extensively assessed and compared these aspects in major organs, such as the liver, kidney, lung, spleen, and…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ahn et al synthesized positively charged N-GQDs from citric acid and PEI, demonstrating successful binding of these N-GQDs with mRNA and pDNA through electrostatic interactions [187]. Similarly, Valimukhametova et al confirmed that N-GQDs and Nd-NGQDs can efficiently form complexes with siRNA through electrostatic interactions [188].…”
Section: Affinity With Biomoleculesmentioning
confidence: 99%
“…After being processed by dedicated enzymes in the cytoplasm, siRNAs bind a sequence of a complementary mRNA by inducing its degradation and preventing the translation in the corresponding protein product. To date, four siRNA-based treatments have been approved by FDA, demonstrating the potential efficacy and safety of this therapeutic approach [146]. Particularly, RNAi through siRNAs appears to be a promising tool to perform a selective gene silencing in the context of targeting tumor-specific mRNAs [84,147].…”
Section: Recent Advances In Sirna Technology and Clinical Applicationsmentioning
confidence: 99%